Mercadeo social y consumo de micronutrientes en Bolivia: el caso de Vitaldía - Cortez, Rafael (2001)
Social marketing means the designing and implementation of strategies aimed at promoting an idea or supporting a certain consumer behavior with philanthropic purposes. Ultimately, it seeks to fostering a consumer choice conducive to social benefits. One extent of social marketing is that of the consumption of health products by women at fertile age. This article presents a methodology for the impact evaluation of an advertising campaign belonging to a broader social marketing strategy supporting a nutritive supplement. Based on Gary Becker's views concerning the effect of advertising over consumption patterns on individuals with stable utility functions, the evaluation methodology aims to measure statistically the causality relationship between the media campaign and the consumption of the nutritive supplement, operating through the effect of advertising over the perception of benefits from the product. The findings confirm empirically the suggested link and unveil that the general campaign on micronutrients works better than the own product's in promoting its consumption.